2020
DOI: 10.1038/s41389-020-0191-6
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A mutants provide proliferating advantage with augmentation of self-renewal activity in the pathogenesis of AML in KMT2A-PTD-positive leukemic cells

Abstract: Acute myeloid leukemia (AML) with partial tandem duplication of histone-lysine N-methyltransferase 2A (KMT2A-PTD) is a subtype of AML and is associated with adverse survival, yet the molecular pathogenesis of KMT2A-PTD is not fully understood. DNA methyltransferase 3A (DNMT3A) is mutated in various myeloid neoplasms including AML, especially at the Arg882. Recently, it has been found that DNMT3A mutations frequently coexisted with KMT2A-PTD and are associated with inferior outcomes. We aimed to understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…A recent study linked high initial KMT2A -PTD RNA levels to poor disease outcomes, however other studies have reported conflicting results [5,35,36]. KASUMI6, derived from a relapsed AML with a dominant negative CEBPA mutation, may provide a useful model to better understand pathogenicity of KMT2A -PTD complexity, whereas many KMT2A -PTD studies have relied on EOL1, which harbors a simple KMT2A -PTD and was derived from a chronic eosinophilic leukemia with a FIP1L1-PDGFRA fusion [6,37].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study linked high initial KMT2A -PTD RNA levels to poor disease outcomes, however other studies have reported conflicting results [5,35,36]. KASUMI6, derived from a relapsed AML with a dominant negative CEBPA mutation, may provide a useful model to better understand pathogenicity of KMT2A -PTD complexity, whereas many KMT2A -PTD studies have relied on EOL1, which harbors a simple KMT2A -PTD and was derived from a chronic eosinophilic leukemia with a FIP1L1-PDGFRA fusion [6,37].…”
Section: Discussionmentioning
confidence: 99%
“…For DNMT3A, a prevailing tumor suppressor function was described [20][21][22] , making a dependency function unlikely. Amid complexity, a tumor-supportive function of mutant DNMT3A was reported in specific AML subsets, e.g., AML driven by a partial tandem duplication in KMT2A 24 . AML-388 harbors a KMT2A-AFDN translocation (Table S2),…”
Section: To the Editormentioning
confidence: 99%
“…Partial tandem duplication of KMT2A (KMT2A-PTD), also named MLL-PTD, is a common genomic aberration in AML. 6 Although many studies have evaluated the prognostic effect of KMT2A-PTD in patients with AML, the results among these studies are still inconsistent. Some studies reported that KMT2A-PTD had a worse prognostic impact on patients with AML, [7][8][9][10] whereas others showed no additional prognostic impact of KMT2A-PTD.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…We used the NOS to evaluate the quality of the 17 cohort studies. The mean score of the 17 included cohort studies was 7.65 (5)(6)(7)(8), indicating that the 17 included studies were of high quality. One study was a phase 3 randomised controlled trial, which was considered to be high quality (online supplemental table 1).…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation